Ultra-processed foods offer in a restaurant at a public university (Research, Society and Development, 2022)
The present study aimed to analyze the supply of ultra-processed foods in the production of meals served to students at a public university, based on the Nova classification, and to verify its adequacy with the recommendations of the Food Guide for the Brazilian Population. Methodology: The list of foods purchased to the preparation of menus for the months of October and November 2019 was analyzed, as well as the sociodemographic data of the students who had their meals in the place. Results: Ultra-processed foods represent 18.79% of total purchased foods; among them, it was observed a higher frequency in the purchase of sweets (35.71%), condiments and sauces (17.85%), followed by cookies and ready-to-eat beverages. Conclusion: The presence of these foods negatively interferes in the quality of the meal served, in addition to representing a risk to the health of the student population that eats at this restaurant. Educational actions for the formation of healthy habits must be implemented or reinforced in order to allow the RU to remain a privileged space for actions to promote the health of the student community, providing healthy, autonomous and conscious food choices.